PENGEMBANGAN MEDIA POPEYE SI PELAUT BERBASIS POWTOON PADA KELAS IV SEKOLAH DASAR - Aliviyah Ayu Nanda (Nusantara Hasana Journal, 2023)
This study aims to develop Powtoon-Based Popeye the Sailor Media on Natural Resources Materials for Grade IV Elementary School. The problem in this research is that teachers use minimal learning media. Teachers tend to only provide material in the form of sharing other people's YouTube links through the class WhatsApp Group. the lack of use of learning media is one of the factors for the low student understanding of the material discussed. In addition, there are still many students who do not understand the material on Natural Resources. Natural Resources is one of the subject matter that has a high level of understanding, one of which is alternative energy sources. Students tend to memorize the material during the learning process. The method used in this research is research and development with the ADDIE development model consisting of Analys (analysis) Design (design) Development (development) Implementation (implementation) Evaluation (Evaluation) And this study uses validation sheets and participant response questionnaires. students to collect data for class. There are 25 students and 4 validators in the research subject. The data collection instrument is by providing validation sheets to be assessed by validators and questionnaire responses to students.Based on the results of the analysis that has been done by the researcher, it was found that the development of Popeye the sailor's learning media based on powtoon was declared very valid because it got a percentage result of 88.3%, and the student's response was said to be feasible with a percentage result of 87.7%. Then the media can be used in learning activities.